PENGEMBANGAN ALGORITMA PENJADUALAN PRODUKSI JOB SHOP UNTUK MEMINIMUMKAN TOTAL BIAYA EARLINESS DAN TARDINESS - Dewi, Dian Retno Sari (Jurnal Ilmiah Teknik Industri, 2005)
This paper develops job shop production scheduling using Non Delay algorithm through forward and backward-forward algorithm to minimize total earliness and tardiness costs. Backward approach has some disadvantages, such as, if the job is scheduled in backward, there is a possibility that the infeasible situation occurs, in which the job is scheduled at t<0. This paper used hypothetic data generated randomly. This job shop scheduling algorithm development was validated using LINDO software to check the effectiveness heuristic method, compared with the optimation method. The validation proves that the result of backward-forward scheduling method is better than the result of forward scheduling method.